Pemberdayaan Masyarakat Desa Senyiur melalui Diseminasi Ekoenzim Limbah Kulit Biji Kopi dan Rumah Tangga untuk Pengelolaan Limbah Ramah Lingkungan di Kecamatan Tanjung, Kabupaten Lombok Utara - ahmad hidayat; Nurul Fadhila; Rudi Pratama (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Community empowerment through the dissemination of eco-enzyme technology made from coffee bean husk waste and household waste represents an environmentally friendly and sustainable waste management initiative. This study aims to introduce and promote the use of eco-enzymes as a solution to reduce waste-related problems in Senyiur Village, Tanjung Subdistrict, North Lombok Regency. The eco-enzymes produced from coffee husk waste and household organic materials can be utilized for various purposes, such as cleaning agents, organic fertilizers, and household waste treatment. Training sessions were conducted to equip the local community with knowledge on simple and effective methods of eco-enzyme production. The outcomes of this training are expected to reduce the volume of improperly managed waste and improve the environmental quality of the village. Moreover, the program has the potential to enhance community income by transforming previously valueless waste into useful products. This initiative is expected to serve as a model for sustainable community empowerment in other areas with similar potential.